The Weddell Gyre heat budget associated with the Warm Deep Water circulation derived from Argo floats - Krissy Anne Reeve; Torsten Kanzow; Olaf Boebel; Myriel Vredenborg; Volker Strass; Rüdiger Gerdes (Ocean Science, 2023)
The Weddell Gyre plays an important role in the global climate system by supplying heat to underneath the ice shelves and in the formation of deep and bottom water masses, which have been subject to widespread warming over past decades. In this study, we investigate the re-distribution of heat throughout the Weddell Gyre by diagnosing the terms of the heat conservation equation for a 1000 m thick layer of water encompassing the core of Warm Deep Water. The spatial distributions of the different advective and diffusive terms in terms of heat tendencies are estimated using gridded climatologies of temperature and velocity, obtained from Argo floats in the Weddell Gyre from 2002 to 2016. While the results are somewhat noisy on the grid scale and the representation of the effects of eddy mixing is highly uncertain due to the need to parameterise them by means of turbulent diffusion, the heat budget (i.e. the sum of all terms) closes (within the uncertainty range) when integrated over the open inflow region in the southern limb, whereas the interior circulation cell remains unbalanced. There is an overall balance in the southern limb between the mean horizontal advection and horizontal turbulent diffusion of heat, whereas the vertical terms contribute comparatively little to the heat budget throughout the Weddell Gyre. Heat convergence due to mean horizontal advection balances with divergence due to horizontal turbulent diffusion in the open southern limb of the Weddell Gyre. In contrast, heat divergence due to mean horizontal advection is much weaker than convergence due to horizontal turbulent diffusion in the interior circulation cell of the Weddell Gyre, due to large values in the latter along the northern boundary due to large meridional temperature gradients. Heat is advected into the Weddell Gyre along the southern limb, some of which is turbulently diffused northwards into the interior circulation cell, while some is likely turbulently diffused southwards towards the shelf seas. This suggests that horizontal turbulent diffusion plays a role in transporting heat both towards the gyre interior where upwelling occurs and towards the ice shelves. Horizontal turbulent diffusion is also a mechanism by which heat can be transported into the Weddell Gyre across the open northern boundary. Temporal deviations from the mean terms are not included due to study limitations. In order to appreciate the role of transient eddying processes, a continued effort to increase the spatial and temporal coverage of observations in the eastern Weddell Sea is required.

High Resolution Water Column Phytoplankton Composition Across the Atlantic Ocean From Ship-Towed Vertical Undulating Radiometry - Astrid Bracher; Hongyan Xi; Tilman Dinter; Antoine Mangin; Volker Strass; Wilken-Jon von Appen; Sonja Wiegmann (Frontiers in Marine Science, 2020)

High-resolution physical–biogeochemical structure of a filament and an eddy of upwelled water off northwest Africa - Wilken-Jon von Appen; Volker H. Strass; Astrid Bracher; Hongyan Xi; Cora Hörstmann; Morten H. Iversen; Anya M. Waite (Ocean Science, 2020)
Nutrient-rich water upwells offshore of northwest Africa and is subsequently advected westwards. There it forms eddies and filaments with a rich spatial structure of physical and biological/biogeochemical properties. Here we present a high-resolution (2.5 km) section through upwelling filaments and an eddy obtained in May 2018 with a TRIAXUS towed vehicle equipped with various oceanographic sensors. Physical processes at the mesoscale and submesoscale such as symmetric instability, trapping of fluid in eddies, and subduction of low potential vorticity (which we use as a water mass tracer) water can explain the observed distribution of biological production and export. We found a nitrate excess (higher concentrations of nitrate than expected from oxygen values if only influenced by production and remineralization processes) core of an anticyclonic mode water eddy. We also found a high nitrate concentration region of ≈5 km width in the mixed layer where symmetric instability appears to have injected nutrients from below into the euphotic zone. Similarly, further south high chlorophyll-a concentrations suggest that nutrients had been injected there a few days earlier. Considering that such interactions of physics and biology are ubiquitous in the upwelling regions of the world, we assume that they strongly influence the productivity of such systems and their role in CO2 uptake. The intricate interplay of different parameters at the kilometer scale needs to be taken into account when interpreting single-profile and/or bottle data in dynamically active regions of the ocean.

Cyclonic eddies and upper thermocline fine-scale structures in the Antarctic Circumpolar Current - Harry Leach; Volker Strass (Ocean Dynamics, 2019)

Modification of the deep salinity-maximum in the Southern Ocean by circulation in the Antarctic Circumpolar Current and the Weddell Gyre - Matthew Donnelly; Harry Leach; Volker Strass (Ocean Dynamics, 2017)

Meteorology and oceanography of the Atlantic sector of the Southern Ocean—a review of German achievements from the last decade - Hartmut H. Hellmer; Monika Rhein; Günther Heinemann; Janna Abalichin; Wafa Abouchami; Oliver Baars; Ulrich Cubasch; Klaus Dethloff; Lars Ebner; Eberhard Fahrbach; Martin Frank; Gereon Gollan; et al. (Ocean Dynamics, 2016)

Modification by lateral mixing of the Warm Deep Water entering the Weddell Sea in the Maud Rise region - Harry Leach; Volker Strass; Boris Cisewski (Ocean Dynamics, 2011)